Baculovirus expression system for magnetic sorting of infected cells and enhanced titer determination - Björn Philipps; Michael Forstner; Lorenz M. Mayr (BioTechniques, 2004)
Recombinant baculoviruses derived from the Autographa californica nuclear polyhedrosis virus (AcNPV) are widely used to express heterologous genes in insect cells, but the use of the baculovirus expression vector system (BEVS) is hampered by slow and tedious procedures for the selection and separation of baculovirus-infected insect cells and for titer determination. Here we developed a new technology based on the bicistronic vector with a fusion protein of the human integral plasma membrane glycoprotein CD4 and green fluorescent protein (GFP) for concomitant expression of target proteins in insect Sf21 cells. Magnetic cell sorting (MACS) technology with anti-CD4 antibody-labeled superparamagnetic beads was used to separate the baculovirus-infected from the noninfected insect cells and therefore to increase the virus titer and to reduce process time. With the herein described use of the MACS-improved baculovirus expression plasmid MACS in baculovirus expression (pMACS-iBac-1), we have been able to select the baculovirus-infected insect cells at an early time point of the infection cycle and therefore enrich the virus titer dramatically. Furthermore, simple end point dilution and GFP fluorescence detection can be used for early and facile detection of recombinant viruses and simplified titer determinations. We show that the bicistronic pMACSiBac-1 with an additional multiple cloning site under the control of the very late promoter polyhedrin (PPH) allows for the expression of target proteins in high amounts, less workloads, and shorter timelines.